Construction of Chromosome Segment Substitution Lines and Inheritance of Seed-Pod Characteristics in Wild Soybean - Zheng, Haiyang; Hou, Lilong; Xie, Jianguo; Cao, Fubin; Wei, Ruru; Yang, Mingliang; Qi, Zhaoming; Zhu, Rongsheng; Zhang, Zhanguo; Xin, Dawei; Li, Candong; Liu, Chunyan; et al. (Frontiers in Plant Science, 2022)
Genetic populations provide the basis for genetic and genomic research, and chromosome segment substitution lines (CSSLs) are a powerful tool for the fine mapping of quantitative traits, new gene mining and marker-assisted breeding. In this study, 213 primary CSSLs were obtained by self-crossing, backcrossing and marker-assisted selection between cultivated soybean (Glycine max [L.] Merr.) variety Suinong14 and wild soybean (Glycine soja Sieb. et Zucc.) ZYD00006. The genomes of these 213 primary CSSLs were resequenced and 580524 SNP markers were obtained, which were divided into 3780 bin markers. A total of 220 secondary CSSLs (from 129 primary CSSLs) covering 89.65% of the ZYD00006 genome were obtained by bin marker detection. The seed pod-related traits were analysed by QTL mapping using a secondary CSSLs. A total of 170 QTLs were detected, and 32 QTLs were detected stably for more than two years. Epistatic analysis showed that there was epistatic interaction between the QTLs or other sites. Furthermore, the hundred seed weight QTL was finely mapped to the region of 64.4 Kb on chromosome 12, and Glyma.12G088900 was identified as a candidate gene. Taken together, a set of wild soybean CSSLs was constructed and upgraded by a resequencing technique. The seed pod-related traits were studied by bin markers, and a candidate gene for the hundred seed weight was finely mapped. our results have revealed the CSSLs can be an effective tool for QTL mapping, epistatic effect analysis and gene cloning.